Multifunctional Biomedical Adhesives. Issue 11 (3rd April 2019) - Pinnaratip, Rattapol; Bhuiyan, Mohammad Saleh Akram; Meyers, Kaylee; Rajachar, Rupak M.; Lee, Bruce P.
Abstract: Currently available biomedical adhesives are mainly engineered to have one function (i.e., providing mechanical support for the repaired tissue). To improve the performance of existing bioadhesives and broaden their applications in medicine, numerous multifunctional bioadhesives are reported in the literature. These adhesives can be categorized as passive or active by design. Passive multifunctional bioadhesives contain inherent compositions and structural designs that can carry out additional functions without added external influences. These adhesives exhibit new functionalities such as antimicrobial properties, self‐healing abilities, the ability to promote cellular ingrowth, and the ability to be reshaped. Conversely, active multifunctional bioadhesives respond to environmental changes (e.g., pH, temperature, electricity, light, and biomolecule concentration), which initiate a change in the adhesive to release encapsulated drugs or to activate or deactivate the bioadhesive for interfacial binding. This review article highlights recent advances in multifunctional bioadhesives. Abstract : This review discusses strategies for engineering multifunctional biomedical adhesives, which involve two general approaches: passive and active design. Passive adhesives contain inherent structural elements that can carry out additional functions without external influences, whereas active adhesives are designed to respond to environmental changes. These adhesives exhibit new functionality such as antimicrobial properties, self‐healing ability, and the capacity to release drugs.